Study of the modern reclamation and ecological state of soils in Azerbaijan - Manafova, Arzu Manaf (Institute of Advanced Engineering and Science, 2024)
For many years in the Republic of Azerbaijan, numerous reclamation and ecological measures aimed at attracting agricultural lands of natural cenoses to use in agrocenoses were carried out. The soils of the studied territory are quite unique in terms of their soil-forming structure and ecological conditions, and they differ from other regions of the country in terms of irrigation water content. The article reflects some important results of soil and water studies conducted over the last years. Determining the qualitative composition of groundwater and irrigation water in different seasons of the year using modern methods is relevant from an environmental and reclamation point of view. Based on remote sensing and geographic information system (GIS) technologies, our research is based on the analysis of natural and anthropogenic landscape changes and changes in natural conditions as a result of agricultural development in the 20 km buffer zone along the banks of Kura and Araz rivers. As a result of the conducted research, it was determined that the rapid growth of the population has caused the reduction of the area of agro-landscapes, the salinization of the soil, the drying of the water in the water basins, the expansion of the construction areas. This has disrupted the natural balance.